The evaluation of serum vitamin D3 in androgenetic alopecia: a case-control study - Kumar, Raj; Iftikhar, Swale; Dubey, Durga Prasad; Singh, Urjasweta; Gupta, Anil Kumar (International Journal of Research in Dermatology, 2024)
Background: Androgenetic alopecia (AGA) is a common hereditary condition characterized by progressive hair loss influenced by androgens. Vitamin D has been implicated in various hair disorders, yet its association with AGA, particularly in South Asian populations, remains inconclusive. Methods: We conducted a case-control study involving 100 male subjects from eastern Uttar Pradesh, India, comprising 50 AGA cases and 50 age-matched controls. Serum vitamin D levels were measured, and participants underwent clinical evaluations. Statistical analyses were performed using unpaired t tests and chi-square tests. Results: Vitamin D deficiency (<20 ng/ml) was significantly more prevalent in AGA cases (56%) compared to controls (24%) (p<0.001), with an odds ratio of 4.0303. Mean serum vitamin D levels were significantly lower in cases (33.1±10.6 ng/ml) than controls (40.3±9.51 ng/ml) (p=0.0005). Severe AGA cases exhibited lower vitamin D levels compared to mild to moderate cases, although the difference was not statistically significant (p=0.32). Conclusions: This study highlights the importance of vitamin D in AGA pathogenesis and suggests the need for routine monitoring of serum vitamin D levels in AGA patients. Further large-scale studies are warranted to confirm these findings and investigate the efficacy of vitamin D supplementation as a therapeutic intervention for AGA.